Mentor, Observe, Support, Take Action (MOST): a model for continuing professional development of teacher leaders - Suryawati, Evi; Syafrinal, Syafrinal; Harfal, Zaldi; Muhson, Ali; Dianti, Putri Rahma; Sulaiman, Nur Ainil (Frontiers in Education, 2024)
This study aims to identify literacy competencies, self-efficacy, and Technological Pedagogical Knowledge (TPK) among Teacher Leaders (TL) as the foundation for developing a model of sustained professional development. The survey involved 153 respondents, TL at the junior high school level in Riau and Riau Islands. Instruments were used to measure literacy skills (environmental, numerical, digital) and TPK employed multiple-choice tests. The questions underwent item analysis, piloted with 30 respondents. A questionnaire measured self-efficacy, the role of TL, and the implementation of the Emancipated Curriculum. Descriptive data analysis determined demographic characteristics and the average competence of TL. Inferential analysis to identify relationships between variables used Structural Equation Modeling (SEM) with Lisrel 8.80 software. Research results reveal that the competence level of TL (literacy, TPK, and self-efficacy) ranges from moderate (60.60) to high (91.20). Based on SEM analysis, the developed model meets the criteria as a well-fitting model. Validation results show that all loading factors are >0.5, t statistics >1.96. This study recommends the development of a TL Professional Development model with the acronym MOST (Mentor, Observe, Support, Take Action) as stages for their professional development to fulfill the mission of moving, acting, and driving the implementation of the Emancipated Curriculum in Indonesia.